Tofacitinib as an adjuvant treatment for pediatric Still's disease - Hou, Ling; Zhou, Peng; Zhao, Chengguang; Wang, Xiuli; Du, Yue (Frontiers in Pediatrics, 2025)
ObjectiveTo describe the efficacy and safety of tofacitinib for pediatric Still's disease, also referred to as systemic-onset juvenile idiopathic arthritis (sJIA). Traditional non-biological drugs and drugs targeting the interleukin-1 and interleukin-6 pathways benefit some patients, but others show inadequate responses.MethodsWe retrospectively analyzed ten patients with pediatric Still's disease who were treated with tofacitinib and had at least one follow-up visit. Data on patient history, laboratory findings, and treatments were collected at disease onset, at the initiation of tofacitinib, and during follow-up.ResultsTofacitinib led to complete remission in six patients, partial remission in three patients, and loss of efficacy in one patient. Among the nine patients with remission, two discontinued corticosteroids entirely and seven used lower dosages of corticosteroids; these patients also used fewer concurrent medications (1 or 2) after tofacitinib initiation. The one patient who experienced loss of efficacy continued to require a higher dosage of corticosteroids and received five different additional medications. The other nine patients received tocilizumab and had a decreased frequency of these injections after tofacitinib initiation. Tofacitinib was well-tolerated, with only one reported instance of an upper respiratory tract infection.ConclusionsTofacitinib appears to be an effective adjunct therapy for management of pediatric Still's disease, particularly for patients with unstable clinical conditions and adverse reactions to corticosteroids.